Decreased Follistatin Levels as a Risk of Acute Sarcopenia Marker in Elderly - Aryana, I Gusti Putu Suka; Winangun, I Made Arya (Cell and BioPharmaceutical Institute, 2023)
Background: Acute sarcopenia is an acute muscle loss that has been associated to the frailty and vulnerability of the elderly. Follistatin has been known as a significant marker for sarcopenia, however, studies of follistatin in humans have shown varying results and there have been no studies to date regarding the relationship between follistatin and acute sarcopenia. The aim of this study was to determine changes in follistatin levels as a risk of acute sarcopenia in elderly.Materials and methods: This study was a prospective observational study involving hospitalized elderly. The follistatin level was examined with enzyme-linked immunosorbent assay (ELISA). Meanwhile the determination of acute sarcopenia was done through the measurement of changes in hand grip strength and calf circumference parameters. The data obtained was descriptively analyzed, followed by bivariate and multivariate analysis. A p<0.05 was considered significant.Results: There were 66 subjects in this study. A total of 10 subjects (15.2%) had acute sarcopenia on the 7th day of hospitalization. The cut-off point of decreased follistatin levels was 4.870 with a sensitivity of 82.1% and a specificity of 60%. There was an association between decreased follistatin levels and acute sarcopenia (p=0.01; RR: 6.90; 95% CI: 1.638-29.069). Multivariate analysis results showed that decreased follistatin levels was a significant factor that might influence the occurrence of acute sarcopenia.Conclusion: Since this study showed that decreased follistatin levels might be a risk of acute sarcopenia in the elderly, thus it could be used as a marker of acute sarcopenia, which should be further investigated.Keywords: decreased follistatin levels, acute sarcopenia, elderly